EMG patterns of the upper limb muscles in the first (flat) and second (topspin) serve performed by a top player - Coutinho, C.; Pezarat Correia, P.; Veloso, A. (Medicine and Science in Tennis, 2004)
Conclusions from the study: Two types of conclusions can be drawn: one concerning the characterisation of the neuromuscular patterns in the serve; and the other concerning the neuromuscular differences between the first (flat) and second (topspin) serve.